Die formule (ἐν ΧρισΤῷ) as basis van die Pauliniese ekklesiologie - Botma, Andre (Hervormde teologiese studies, 1996)
The formula (ἐν ΧρισΤῷ) as the basis of Pauline ecclesiology. This article is an attempt to interpret the Pauline formulaἐν ΧρισΤῷ. The argument proceeds from the thesis that the formula forms the basis of Pauline ecclesiology. Firstly, traditional interpretations of the formula are shown to be inadequate since they understand the phrase one-sidedly as a reference to the kerugma of the cross. It is argued instead, as a second step, that theformula should be understood in terms ofparticipation in the 'Jesus-Sache'. This expression encapsulates Paul's intention that the believer should 'become as Jesus was' Participation and reconciliation, ethics and Suffering thus cohere. In conclusion, the meaning of the formula ἐν ΧρισΤῷ is further explicated by juxtaposing it with the phrase ἐν ΧρισΤῷ The interpretation of the genitive as subjective implies that the believer should 'believe as Christ believed'. To participate in the 'Jesus-Sache' thus means to become part of the church.